PENGARUH TREN HOME DÉCOR DI INSTAGRAM TERHADAP MOTIVASI KONSUMEN DALAM MEMBELI PRODUK BERBAHAN SERAT ALAM - Nur, Christmastuti (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2018)
Instagram is one of the most popular social media in Indonesia because there are at least 53 million active users. Nowadays, one of the popular trends among Instagram users in Indonesia is home décor. Moreover, there are high amount numbers of Instagram accounts that upload photos of minimalist home decor with Scandinavian design style. The high enthusiasm of Instagram users toward the trend of home décor is followed by the desire to decorate their residence with home decorating products such as natural products made of natural fiber. This research aims to determine the effect of home décor trends in Instagram on consumer motivation in buying products made of natural fibers. The method used in this study is the observation and in-depth interviews toward consumers of home décor product in Instagram with descriptive analysis approach. The results of this research are home décor trend in Instagram has an effect on consumer motivation in buying product made from natural fiber. However, the trend is not the primary motivation in buying home décor products made from natural fiber, but rather consider factors of usability, hobbies, and design. Therefore, even if home décor trends will pass, the market for natural fiber products will remain, especially if natural fiber products have a variety of new usability alternatives.